Late Glacial and Holocene Paleoenvironmental Reconstruction of the Submerged Karst Basin Pirovac Bay on the Eastern Adriatic Coast - Nikolina Ilijanić; Dea Brunović; Slobodan Miko; Valentina Hajek Tadesse; Ozren Hasan; Ivan Razum; Martina Šparica Miko; Saša Mesić (Journal of Marine Science and Engineering)
This study focuses on the analysis of sediment core retrieved from the deepest part (25 m) of Pirovac Bay. A long sedimentary sequence (7.45 m) supplemented by a shorter sediment core (1.45 m) from a shallower part of the bay was analyzed for sedimentological, mineralogical, geochemical, and micropaleontological (ostracod) parameters. The sediment thickness above the underlying karst paleorelief (karstic bedrock) is up to 12 m. Sediments recorded a transition from a freshwater to a marine environment starting from post-Neapolitan Yellow Tuff tephra sedimentation. First, the floodplain developed in Pirovac Bay, with intermittent pools and ponds, followed by wetland environment. The formation of a shallow freshwater paleolake during the Middle Holocene at 10 cal kyr BP was enabled by the rising sea level and high freshwater input from the karstified underground from the adjacent Lake Vrana (Biograd na Moru). The onset of marine intrusions through the karstified underground is evident with formation of a brackish lake in the Pirovac Bay basin. Marine transgression and flooding of the bay occurred at 7.3 cal kyr BP, evidenced by the geochemical and ostracod parameters, providing crucial insights into the dynamics of coastal inundation under past climate change. Intriguingly, freshwater ostracod species were still present in the marine sediments, brought into the bay from Lake Vrana through surficial canal Prosika and groundwater discharge (numerous estavelles) along the northeastern shores of the bay, proving their mutual influence. This submerged Holocene freshwater paleolake, reported here for the first time, underlines the sensitivity of coastal karst systems to the rise in sea level and serves to stress how important understanding of these processes is for effective management in coastal zone and climate change adaptation strategies. The findings provided evidence supporting the existence of coastal marine basins as freshwater lakes prior to being flooded by seawater as a consequence of the Holocene post-glacial sea level rise.